Pickering emulsion loaded with total flavonoids from Dracocephalum moldavica L. potentially promotes angiogenesis in the ischemic penumbra after cerebral ischemia reperfusion - Gao, Tianyi; Wu, Lu; Ma, Yuru; Zhai, Weikai; Zhang, Lu; Cong, Wei; Cai, Zhiping; Cui, Chengli; Li, Liang (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundIschemic stroke is a major disease threatening human health. Currently, its therapeutic options are extremely limited, and common thrombolytic therapy tends to cause tissue damage. Traditional Chinese and Ethnic Medicine have a centuries-long clinical history in treating ischemic stroke. Dracocephalum moldavica L., a traditional Mongolian herb distributed in China’s Inner Mongolia, is one such example.MethodsWe adopted the ultrasonic extraction method to obtain total flavonoids from Dracocephalum moldavica L. (TFDM) and validated its efficacy in an animal model of ischemia-reperfusion injury. A novel Pickering emulsion was used to load TFDM as a new delivery system, and we characterized its key properties such as physical properties and bioavailability.ResultsThe extraction efficiency of TFDM obtained by the ultrasonic extraction method was improved, with the extraction rate of the new protocol reaching 65% compared with the traditional method. Subsequent animal model validation confirmed that TFDM extracted by this method had significant therapeutic effects: enhancing vascular perfusion in the ischemic penumbra after reperfusion, reducing cerebral infarct volume, and promoting neurological function recovery. Mechanistically, TFDM upregulated the expression of VEGF, VEGFR2, and CD34 in the ischemic penumbra of cerebral ischemia-reperfusion injured rats post‐injury. Concomitantly, these molecular changes accelerated microvascular regeneration and microcirculation reconstruction in the ischemic penumbra. Further studies have confirmed that the delivery strategy using Pickering emulsion to load TFDM can effectively overcome the inherent drawbacks of TFDM, such as its short storage time and low bioavailability.ConclusionOverall, this study provides robust evidence for TFDM’s neuroprotective effects, supporting its potential as a novel therapeutic candidate for stroke prevention and treatment. Notably, TFDM encapsulated in Pickering emulsion is a practical, efficient approach with promising prospects for future stroke therapy.